THE RELATIONSHIP OF LANDEK KARO TRADITIONAL DANCE AND THE CHARACTER EDUCATION OF CHILDREN IN SIOSAR VILLAGE KABUPATEN KARO - Fanesa Anastasya Br Depari; Rumiris Lumbangao; Ribka Kariani Br Sembiring; Darinda Sofia Tanjung (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This research aimed to assess and determine the relationship between the Landek Karo traditional dance and character education among children aged 9 to 13 years in the relocation area of Mount Sinabung, Siosar Village, Pertibi Lama, Kecamatan Merek, Kabupaten Karo, North Sumatra. The population of this research consisted of 156 children aged 9 to 13 years in Siosar Village. The samples were selected through purposive sampling; in this case, the researcher chose 35 children aged 9 to 13 years who were dancers in the Siosar Festival event held in September 2019 in Siosar Village. This research employed a quantitative survey method, which aimed to analyze the research results using t-test hypothesis testing. The findings indicated that the average t-count score for the Landek Karo traditional dance was 24.843, which was greater than the t-table value of 1.683 and categorized as high. Similarly, the average t-count score for character education was 24.843, which was also greater than the t-table value of 1.683 and categorized as high. Therefore, Ho was accepted, indicating that there was a relationship between the Landek Karo traditional dance and the character education of children in Siosar Village, Kabupaten Karo.